Genetic variation in KRTAP11.1 gene of Suri alpaca (Vicugna pacos) from Puno, Peru - Gallegos, Roberto (2019)
The objective of this study was to identify genetic single nucleotide polymorphisms (SNPs) in the coding region of the KRTAP11.1 gene from the Suri alpaca population from Puno, Peru. Genomic DNA (n = 119) was used to amplify the 636 bp fragment of the coding region from the KRTAP11.1 gene. The polymerase chain reaction products of the KRTAP11.1 gene were sequenced by both strands and polymorphism type SNPs were identified. All SNPs (n = 3) were in Hardy-Weinberg equilibrium and had a high level of genotypic linkage disequilibrium with the presence of two haplotypes. All genetic polymorphisms generate non-synonymous amino acids changes: SNP 110 T>G (Ser>Ala), SNP 363 T>G (Phe>Cys) and SNP 375 A>C (Tyr>Ser). The results indicated the presence of moderate genetic diversity in the coding region of the KRTAP11.1 gene from the Suri alpaca population.